Santal folk tales - Bodding, P. O. (New Delhi: Gyan Publishing House, 2007)
Bodding's Santal Folk Tales is the only comprehensive repository of Santal folklore. Such tales and traditions have lived on the lips and in the hearts of the Santals for centuries. Undoubtedly these are genuine folk tales which have been noted down by a Santal whose horizon was limited to Santal people, their areas and traditions. It is not difficult to trace Aryan influence on these stories and sometimes we can point to parallel tales in the well-known collections of Aryan tales. Yet these are real folk tales of the Santals, entirely of indigenous growth. Jackal, for instance, is a conspicuous and important character in many Santal folk tales. It is not unlikely that it originally belonged to Santal tribes and later adopted by Aryans. Stories about women, animals born by women, ogres and some miscellanesous are educational and entertaining tales which are the mirror of Santal culture. A common trait of the Santals is their keen sense of humour. They are able to see the funny side of a situation and do not mind joking at themselves. There is a whole volume devoted to humorous tales. This rich treasure of genuine folk tales keeps alive the vibrant Santali culture and tradition and let others enjoy it.